2015
DOI: 10.1111/birt.12154
|View full text |Cite
|
Sign up to set email alerts
|

Routine Use of an Antenatal Infection Screen‐and‐Treat Program to Prevent Preterm Birth: Long‐Term Experience at a Tertiary Referral Center

Abstract: Long-term results support the use of an antenatal infection screen-and-treat program to prevent preterm birth. If integrated into routine pregnancy care at a high-risk obstetrical setting, this simple public health intervention could lead to a significant reduction in preterm birth, low infant birthweight, and adverse pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 18 publications
4
49
1
Order By: Relevance
“…5,6 In a study by Farr and Kiss, routine antenatal screening for Candida and Trichomonas vaginalis and treating them was found to be associated with significantly lower risk (nearly 2.5 times lower) of preterm birth. 7 Similar observation was made in an open label placebo controlled randomized trial, 6 where the authors found that treatment of asymptomatic Candida infection is associated with lower risk (OR 0.33) of preterm delivery.…”
Section: Discussionsupporting
confidence: 61%
“…5,6 In a study by Farr and Kiss, routine antenatal screening for Candida and Trichomonas vaginalis and treating them was found to be associated with significantly lower risk (nearly 2.5 times lower) of preterm birth. 7 Similar observation was made in an open label placebo controlled randomized trial, 6 where the authors found that treatment of asymptomatic Candida infection is associated with lower risk (OR 0.33) of preterm delivery.…”
Section: Discussionsupporting
confidence: 61%
“…For this reason, our department has integrated a program for all pregnant women, to screen and treat for the asymptomatic colonization with pathogens, including bacterial vaginosis and vaginal candidosis [11]. As it is known that recurrent vulvovaginal candidosis can be harmful during early pregnancy, the need for early detection and adequate antifungal treatment is clearly emphasized [10].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published Austrian study, implemented following the results of a randomized clinical trial, retrospectively analyzed the pregnancy outcome data of over 17,000 women at high risk of PTB (based on general, family, and obstetric risk factors) across a 10-year timespan following introduction of a voluntary antenatal infection “screen and treat” program (122). All women received standard antenatal care; 49.5% entered the screen and treat program, which consisted of testing of vaginal swabs at 10- to 16-week gestation for detection of BV and presence of Candida spp.…”
Section: Prevention Of Infection-driven Ptbmentioning
confidence: 99%
“…The effect of the program on the rates of early/extreme PTB was particularly impressive, with a more than 77% reduction observed; this is consistent with the known role of intrauterine infection in the majority of deliveries <32 weeks. The major weakness in this study is its retrospective, non-randomized design, although confounding is minimal and unlikely to alter the findings (122). …”
Section: Prevention Of Infection-driven Ptbmentioning
confidence: 99%